Neil Gaiman library Volume 2 - Gaiman, Neil; Buckingham, Mark; Doran, Colleen, 1963-; Bolton, John, 1951-; Zulli, Michael; Klein, Todd; Starkings, Richard; Levine, Jason; Moon, Fabio (Milwaukie, OR : Dark Horse Books, 2020)
A deluxe oversized collection of comic stories from celebrated and award-winning writer Neil Gaiman, in conjunction with some of comics' most acclaimed creators. In these four essential Gaiman tales, a group of friends search for a mysterious circus that is either a dream or nightmare, a string of bizarre occult events befall strangers from all walks of life, a woman is given the gift of a Harlequin's heart, and a young boy is followed by monsters and regrets that last a lifetime. Collects the full graphic novels The Facts in the Case of the Departure of Miss Finch, Likely Stories, Harlequin Valentine, and Troll Bridge in a single deluxe hardcover volume with a dust jacket.
Likely stories / stories and words by Neil Gaiman ; art and adaptation script Mark Buckingham -- Troll bridge / stories and words by Neil Gaiman ; art Colleen Doran ; lettering Todd Klein -- Harlequin Valentine / stories and words by Neil Gaiman ; art John Bolton ; lettering Richard Starkings and Comicraft's Jason Levine -- The facts in the case of the departure of Miss Finch / stories and words by Neil Gaiman ; art Michael Zulli ; script adaptation and lettering Todd Klein -- Bonus content (Likely stories ; Troll bridge ; Harlequin Valentine).
115884
Keywords: Harlequin (Fictitious character); Man-woman relationships; Circus; Monsters; Fictional Work; Comics (Graphic works); Fiction; Graphic novels